Evaluating welfare and economic effects of raised fertility - Krzysztof Makarski; Joanna Tyrowicz; Magda Malec (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2019)
Many countries consider rising fertility through pro-family policies as a solution to the fiscal pressure stemming from longevity. However, an increased number of births implies immediate private costs and only delayed public benefits of younger and larger population. We propose using an overlapping generations model with a rich family structure to quantify the effects of simulated increases to the birth rates. We analyze the overall macroeconomic and welfare effects of these simulated paths relative to status quo. We also study the distribution of these effects across cohorts and study the sensitivity of the final effects to the assumed target value and path of increased fertility. Since our study tries to quantify the possible effects of pro-natalistic policies, we focus of public costs and benefits of having children. We find that fiscal effects are positive, but short of the natalistic expenditures in many countries. The sign and the size of both welfare and fiscal effects depend on the patterns of increased fertility.
Keywords: H55; E17; C60; C68; E21; D63; 330; fertility; welfare; natalistic policies; overlapping generations model